Age-related Changes in Lateral Entorhinal and CA3 Neuron Allocation Predict Poor Performance on Object Discrimination - Maurer, Andrew P.; Johnson, Sarah A.; Hernandez, Abbi R.; Reasor, Jordan; Cossio, Daniela M.; Fertal, Kaeli E.; Mizell, Jack M.; Lubke, Katelyn N.; Clark, Benjamin J.; Burke, Sara N. (Frontiers in Systems Neuroscience, 2017)
Age-related memory deficits correlate with dysfunction in the CA3 subregion of the hippocampus, which includes both hyperactivity and overly rigid activity patterns. While changes in intrinsic membrane currents and interneuron alterations are involved in this process, it is not known whether alterations in afferent input to CA3 also contribute. Neurons in layer II of the lateral entorhinal cortex (LEC) project directly to CA3 through the perforant path, but no data are available regarding the effects of advanced age on LEC activity and whether these activity patterns update in response to environmental change. Furthermore, it is not known the extent to which age-related deficits in sensory discrimination relate to the inability of aged CA3 neurons to update in response to new environments. Young and aged rats were pre-characterized on a LEGO© object discrimination task, comparable to behavioral tests in humans in which CA3 hyperactivity has been linked to impairments. The cellular compartment analysis of temporal activity with fluorescence in situ hybridization for the immediate-early gene Arc was then used to identify the principal cell populations that were active during two distinct epochs of random foraging in different environments. This approach enabled the extent to which rats could discriminate two similar objects to be related to the ability of CA3 neurons to update across different environments. In both young and aged rats, there were animals that performed poorly on the LEGO object discrimination task. In the aged rats only, however, the poor performers had a higher percent of CA3 neurons that were active during random foraging in a novel environment, but this is not relate to the ability of CA3 neurons to remap when the environment changed. Afferent neurons to CA3 in LEC, as identified with the retrograde tracer choleratoxin B (CTB), also showed a higher percent of cells that were positive for Arc mRNA in aged poor performing rats. This suggests that LEC contributes to the hyperactivity seen in CA3 of aged animals with object discrimination deficits and age-related cognitive decline may be the consequence of dysfunction endemic to the larger network.